Diseño y construcción de herramienta de medición in situ a incidencia normal de coeficiente de absorción de materiales no convencionales basado en la ISO 10534-1 (2019)
This brief overview shows in detail the process of research and development for the construction and fine tuning of a type in-situ, Kundt's tube based on ISO 10534-1 standard, this tool is used in the measurement of the absorption coefficients of different acoustic materials, its preparation follows the proposed construction methodologies and subsequently performs comparison in their performance to a classical Kundt's tube. The processing of the data extracted from the measurement activities are analyzed using the technique of randomized experiments helped of a software tool of statistics, resulting in that the behavior of made tube handmade presents a response which, although statistically it shows differences, these follow the behavior of the classic tube provided by Universidad de San Buenaventura. Finally, it can be concluded that within the tube manufacturing process on-site employed common materials of easy acquisition achieving a behavior similar to the classic tube as well as having a portable measuring element